Effects of different feeding regimes on juvenile black rockfish (Sebastes schlegilii) survival, growth, digestive enzyme activity, body composition and feeding costs. (30th June 2020) - Guo, Haoyu; Roques, Jonathan A. C.; Li, Miao; Zhang, Xiumei
Abstract: The objective of this study was to establish a proper feeding regime for juvenile black rockfish ( Sebastes schlegilii ) intended for stock enhancement. We used a combined experimental design to assess the effects of different feeding rates (1%, 3% and 5% body weight per day (BW/day)) and feeding frequencies (apparent satiety or restricted feeding 1 to 3 times daily) on survival, growth, digestive enzyme activity, body composition and feeding costs over 50 days, from newly weaned (initial average weight 1.5 ± 0.2 g) to release size. The results showed that feeding rate significantly affected fish growth, feed utilization and body composition. The highest feed conversion ratio was at 3% BW/day. Increased feeding rates resulted in enhanced growth and higher body lipid content, but this was also accompanied by decreased contents of moisture, protein and ash. With feeding to apparent satiety, increased feeding frequency resulted in higher growth performance and enhanced intestinal lipase activity but decreased gastric protease activity. There were no growth improvements or effects on digestive enzyme activity and body composition with increasing feeding frequency (from one to three times daily) under a fixed‐quantify feeding (3% BW/day). Feed costs increased with increasing feeding rates or apparent satiety feeding frequencies and were associated with shorter growth times to reach a suitable size for release. Our study suggests that a feeding rate of 3% BW/day is the best feeding regime for proper growth and reduced feed costs in juvenile black rockfish before releasing for stock enhancement.